2011
DOI: 10.1212/wnl.0b013e318216715e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of UV exposure to prevalence of multiple sclerosis in England

Abstract: Objective: To assess the potential relationship of ultraviolet B radiation (UVB) and Epstein-Barr virus (EBV) exposure in explaining the period prevalence of multiple sclerosis (MS) in England. Methods: English national Hospital Episode Statistics covering all admissions to National HealthService hospitals in England in the 7 years from 1998 to 2005 were used to obtain the period prevalences of MS and infectious mononucleosis (IM) in England. The United States National Aeronautics and Space Administration's da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…Multiple studies showed that 25-OH vitamin D levels are lower in MS cases compared to controls in both European-descended and African American populations (Munger et al, 2006;Islam et al, 2007;Gelfand et al, 2011;Ramagopalan et al, 2011b (Ramagopalan et al, 2009). Vitamin D receptor-binding elements have been identified in the majority of MS-associated genes, implying that expression of many of these genes could also be controlled by vitamin D (Ramagopalan et al, 2010).…”
Section: Vitamin D Geneticsmentioning
confidence: 99%
“…Multiple studies showed that 25-OH vitamin D levels are lower in MS cases compared to controls in both European-descended and African American populations (Munger et al, 2006;Islam et al, 2007;Gelfand et al, 2011;Ramagopalan et al, 2011b (Ramagopalan et al, 2009). Vitamin D receptor-binding elements have been identified in the majority of MS-associated genes, implying that expression of many of these genes could also be controlled by vitamin D (Ramagopalan et al, 2010).…”
Section: Vitamin D Geneticsmentioning
confidence: 99%
“…It is an inflammatory and degenerative disease of the central nervous system characterized by demyelination and axonal loss. A pronounced latitudinal gradient in MS prevalence starting at about 428 of latitude implicates solar wavelengths in the UVB range [66][67][68] (figure 2). This is also indicated by a month-of-birth effect, and changes in the timing of the month-ofbirth effect according to the strength of UVB.…”
Section: Diseases Related To Uvb Exposure Insufficient To Maintain Admentioning
confidence: 99%
“…Multiple sclerosis is more common in people who live far from the equator (59). Distribution of MS is explained by ultraviolet B radiation exposure (8,45,46). MS relates to an interaction between genetic factors and vitamin D deficiency (5,56,57,60).…”
Section: Discussionmentioning
confidence: 99%
“…The separate areas are recognized as inflammation, demyelination, axonal loss, and gliosis (plaques) in the CNS (4). Different factors, such as autoimmune mechanisms, genetic background (5-7), and environmental factors (8)(9)(10)(11), have been known to play roles in the occurrence of MS even though the main etiology of this disease is unidentified.…”
Section: Introductionmentioning
confidence: 99%